2000
DOI: 10.1152/ajpendo.2000.279.2.e323
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone decreases muscle glutamine production and stimulates protein synthesis in hypercatabolic patients

Abstract: We determined the effects of 24-h recombinant human growth hormone (rhGH) infusion into a femoral artery on leg muscle protein kinetics, amino acid transport, and glutamine metabolism in eight adult hypercatabolic trauma patients. Metabolic pathways were assessed by leg arteriovenous catheterization and muscle biopsies with the use of stable amino acid isotopes. Muscle mRNA levels of selected enzymes were determined by competitive PCR. rhGH infusion significantly accelerated the inward transport rates of pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 39 publications
(72 reference statements)
1
30
0
1
Order By: Relevance
“…Concentrations of selected amino acids (phenylalanine, leucine, and glutamine) and isotopic enrichment of L-[ring-2 H 5 ]phenylalanine were measured in plasma samples taken from the radial artery and femoral vein, as previously described (21,22). The stable isotopes L- [1-13 C]phenylalanine, L-[1-13 C]leucine, and L- [5-15 N]glutamine were added to the tubes as internal standards (22).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrations of selected amino acids (phenylalanine, leucine, and glutamine) and isotopic enrichment of L-[ring-2 H 5 ]phenylalanine were measured in plasma samples taken from the radial artery and femoral vein, as previously described (21,22). The stable isotopes L- [1-13 C]phenylalanine, L-[1-13 C]leucine, and L- [5-15 N]glutamine were added to the tubes as internal standards (22).…”
Section: Patientsmentioning
confidence: 99%
“…The stable isotopes L- [1-13 C]phenylalanine, L-[1-13 C]leucine, and L- [5-15 N]glutamine were added to the tubes as internal standards (22). To determine the enrichment of the infused tracer and the internal standards of free phenylalanine, leucine, and glutamine in the plasma, the t-butyldimethylsilyl derivatives were prepared as described by Biolo et al (21). Tracer/tracee ratios were measured by gas chromatography-mass spectrometry analysis (Hewlett-Packard 5985) (21).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated that rhGH had beneficial effects on stimulating body protein syntheses and producing nitrogen-spacing effects [6,[12][13][14] . However, the impact of rhGH on body proteins and the change in blood glucose levels have not been previously investigated in patients receiving PN or EN following elective gastrointestinal surgeries [15][16][17] . In the present experiment, we observed the effect of rhGH on nitrogen balance, plasma proteins and blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that rhGH can stimulate body protein synthesis and produce nitrogenspacing effects [11][12][13] . However, the impact of rhGH on body trace elements and blood glucose has not been investigated in patients receiving PN or EN following selective gastrointestinal surgery [14][15][16] . In the present experiments, we studied the effects of rhGH on trace element metabolism and blood glucose.…”
Section: Discussionmentioning
confidence: 99%